Assessment of the Quality of Life in Elderly and Senile Age Patients with Chronic Heart Failure - Olga A Osipova; Tatiana P Golivets; Igor I Khamnagadaev; Elena V Gosteva; Oksana N Belousova (Mashhad University of Medical Sciences, 2022)
Background: The Improvement of quality of life (QOL) and its dynamics among patients with chronic heart failure (CHF) is an important task and one of the leading criteria for the therapy effectiveness among patients with CHF.Aim: The present study aimed to compare the QOL in patients with heart failure with mid-range ejection fraction (HFmrEF) in different age groups, taking into account gender differences.Method: This cross-sectional study was conducted on 377 participants with CHF and a control group of 30 subjects matched in age without CHF in Belgorod, Russia, in 2020. The participants were selected by the purposive sampling method. All patients were assigned into three groups, including middle age, elderly age, and senile age. The participants completed the Minnesota Living with Heart Failure Questionnaire (MLHFQ), Zung Self-Rating Anxiety Scale, and Zung Self-Rating Depression Scale. The collected data were analyzed with nonparametric statistic methods.Results: It was revealed that the QOL was significantly lower in patients with HFmrEF of ischemic genesis than in the control group. The lowest QOL, according to the MLHFQ questionnaire, was revealed in old age. In the female population, the QOL was significantly lower than in men in the same age group. Moreover, the most pronounced manifestations of anxiety and depressive disorders were observed in middle-aged men and middle-aged women, respectively.Implications for Practice: According to the findings of this study, it is suggested that physicians and therapists pay special attention to the QOL of the elderly and senile aged people with CHF.